Evaluation of Etiology of Epistaxis and its Management in Dhulikhel Hospital - Shrestha, I; Pokharel, M; Shrestha, BL; Dhakal, A; Amatya, RCM (Kathmandu University Medical Journal, 2015)
Background Epistaxis is one of the most common and most difficult emergencies presenting in 7-14% of the general population each year. Although its lifetime incidence is about 60%, only 6% require formal medical intervention but they can be serious and even life threatening. Objective The main objectives are to study different etiology, types, modality of treatment of epistaxis. Specific objective is also to find out if the modality of treatment is associated with age, site, amount of bleeding and etiology. Method It is a prospective, cross sectional, longitudinal, analytical study done in Department of ENT, Dhulikhel hospital, Kathmandu University School of Medical Sciences (KUSMS) from Aug. 2010 to Aug. 2013. Data was collected. This study was cleared through institutional review committee of hospital. Statistical analysis was done using SPSS 16.0. Result 487 patients were studied during the period. There was significant association between age group with type of treatment (p value 0.002); and with admission (p value < 0.001). Significance in the study was also shown in the correlation between site of bleeding and the type of treatment and also with alcohol intake with site of bleeding (p value < 0.001).However there was no significance between hypertension and the type of treatment methods chosen (p value >0.01). Conclusion Management of epistaxis is challenging. Most are managed by non surgical means whereas some by surgical treatment. Non surgical treatment is still useful, safe and cost effective. Type of treatment and need for hospital stay is related to age and site of bleeding. Kathmandu University Medical Journal Vol.13(1) 2015; 49-55